Pengaruh Kadar Air dan Ketebalan Papan Terhadap Laju Pengeringan Kayu Karet (Hevea brasiliensis) dengan Penerapan Fase Pendinginan : The Effect of Water Content and Thickness of Rubber Wood (Hevea brasiliensis) Board on The Drying Rate with the Application of the Cooling Phase - Wijayanto, Arip (Jurnal Silva Tropika, 2024)
ABSTRACT Rubber wood is one of the wood species used as furniture raw material. Before processing it into furniture, it needs to be dried first until the moisture content meets the SNI requirements. In this study, drying data for rubber wood with different initial moisture content at several different thicknesses were taken from a furniture company in Central Java and then analyzed descriptively using Microsoft Excel. In the drying process, the company applies a cooling phase in between the heating phases. The results of the data analysis show that drying wood with a thickness of 30 mm takes longer than that with a thickness of 25 mm. On the other hand, in the same initial moisture content range, rubber wood with a thickness of 30 mm has a drying rate that is smaller than the drying rate for wood with a thickness of 25 mm. In the higher moisture content ranges the wood drying rate is greater than rubber wood with a low initial moisture content.   Keywords: cooling phase, drying, moisture content, rubber wood, thickness   ABSTRAK Salah satu jenis kayu yang digunakan sebagai bahan baku furnitur adalah kayu karet. Sebelum diolah menjadi furnitur kayu karet perlu dikeringkan terlebih dahulu sampai kadar airnya memenuhi persyaratan SNI tentang kayu untuk furnitur. Penelitian ini data pengeringan kayu karet dengan kadar air awal berbeda pada beberapa jenis ketebalan berbeda diambil dari perusahaan furnitur di Jawa Tengah dan kemudian diolah secara deskriptif menggunakan microsoft excel. Proses pengeringan di perusahaan tersebut menerapkan fase pendinginan di sela-sela fase pemanasan. Hasil pengolahan data menunjukkan bahwa pengeringan kayu ketebalan 30 mm membutuhkan waktu yang lebih lama dibandingkan ketebalan 25 mm. Sebaliknya, pada rentang kadar air awal yang sama kayu karet dengan ketebalan 30 mm memiliki laju pengeringan yang lebih kecil dibandingkan laju pengeringan kayu ketebalan 25 mm. Rentang kadar air yang lebih tinggi laju pengeringan kayu lebih besar dibandingkan kayu karet dengan kadar air awal yang rendah.   Kata kunci: fase pendinginan,kadar air, kayu karet, ketebalan,  pengeringan